2014
DOI: 10.3390/mi5041296
|View full text |Cite
|
Sign up to set email alerts
|

Laser Controlled Synthesis of Noble Metal Nanoparticle Arrays for Low Concentration Molecule Recognition

Abstract: Nanostructured gold and silver thin films were grown by pulsed laser deposition. Performing the process in an ambient gas (Ar) leads to the nucleation and growth of nanoparticles in the ablation plasma and their self-organization on the substrate. The dependence of surface nanostructuring of the films on the deposition parameters is discussed considering in particular the number of laser pulses and the ambient gas nature and pressure. The performance of the deposited thin films as substrates for surface-enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…5d–i , the small and medium particles are seen to form random networks with the medium-sized particles sparsely covering the surface and the small ones more densely distributed across the irradiated region (see Supplementary Note 2 ). The formation of NPs is believed to come from the combination of thermal effects 31 32 33 34 and the redeposition of particles following laser ablation 17 15 . Upon close examination of the SEM images, it appears that the small particles are in reality approximately hemispherical, an observation supported by a cross-section of a coloured silver sample obtained through focused ion beam milling and imaging.…”
Section: Resultsmentioning
confidence: 99%
“…5d–i , the small and medium particles are seen to form random networks with the medium-sized particles sparsely covering the surface and the small ones more densely distributed across the irradiated region (see Supplementary Note 2 ). The formation of NPs is believed to come from the combination of thermal effects 31 32 33 34 and the redeposition of particles following laser ablation 17 15 . Upon close examination of the SEM images, it appears that the small particles are in reality approximately hemispherical, an observation supported by a cross-section of a coloured silver sample obtained through focused ion beam milling and imaging.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the formation of decorated NWs can be explained in terms of the NP formation process proposed by Fazio et al in conjunction with the mechanism for the formation of NWs/fibers explained above [35]. In short, the laser pulses locally melt the target and produce an ablation plume where the NPs are formed.…”
Section: Discussionmentioning
confidence: 96%
“…Fazio et al observed the formation of Au and Ag nanoparticles formed by laser ablation in an Ar atmosphere (which matches our experimental situation). The NPs form in the ablation plume and are subsequently deposited in a self-organized manner over solid substrates placed directly in front of the target [35]. The same process of NP formation followed by deposition has been observed in ablated Au and Ag surfaces (among other metals) [36].…”
Section: Discussionmentioning
confidence: 99%
“…The application of the laser ablation (LA) technique covers a great variety of scientific and technological fields: Pulsed Laser Deposition (PLD) [ 1 ], nanoparticles production [ 2 ], Laser Induced Breakdown Spectroscopy (LIBS) for chemical analysis of solid materials [ 3 ], high-precision artwork restoration [ 4 ], investigation of the conditions for inertial confinement fusion [ 5 ]. Despite being so widely used, LA is far from being completely understood.…”
Section: Introductionmentioning
confidence: 99%